Efficacy and safety of prostaglandin drugs for elevated intraocular pressure: a Bayesian network meta-analysis - Jieting Peng; Wenrui Huang; Junguo Duan (Frontiers in Medicine)
ObjectiveTo evaluate and compare the effectiveness and safety of latanoprost, bimatoprost, travoprost, and tafluprost in lowering intraocular pressure (IOP) in individuals with glaucoma or ocular hypertension.MethodsWe searched PubMed, Embase, Web of Science, and the Cochrane Library for randomized controlled trials (RCTs) published up to April 2025 comparing latanoprost, bimatoprost, travoprost, and tafluprost in adults with glaucoma or ocular hypertension. Primary outcomes were IOP reduction and conjunctival hyperemia. We assessed study quality using the Cochrane Risk of Bias 2.0 tool. Evidence certainty was evaluated with the CINeMA framework. A Bayesian network meta-analysis was conducted in RStudio. This review is registered with PROSPERO (CRD420251034803).Results25 RCTs published between 2001 and 2024, involving 4,045 participants, were included. All studies compared monotherapy with latanoprost, bimatoprost, travoprost, or tafluprost. Among these, bimatoprost showed the most effective reduction in intraocular pressure compared to latanoprost [mean difference (MD) 0.69; 95%confidence interval (CI) 0.28–1.1; SUCRA 95.6%; moderate confidence]. It also performed significantly better than travoprost (MD 0.64; 0.14–1.09; 39.2%; low confidence). No other comparisons showed statistically significant differences. Overall, the quality of evidence for this outcome ranged from low to moderate. In terms of safety, 16 trials, including 3,119 participants, reported on conjunctival hyperemia. Both bimatoprost [odds ratio (OR) 3.3; 2.5–4.5; 18.4%, high confidence] and travoprost (0.46; 0.33–0.63; 55%, high confidence) were associated with a higher risk of hyperemia compared to latanoprost. Bimatoprost also posed a significantly greater risk than travoprost (1.51; 1.06–2.16, high confidence).ConclusionBimatoprost provided the greatest IOP reduction but carried a higher risk of conjunctival hyperemia. Latanoprost and tafluprost offered balanced efficacy with better tolerability, making them suitable for patients with mild disease.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251034803.